Atrioesophageal Fistula after Minimally Invasive Video-Assisted Epicardial Ablation for Lone Atrial Fibrillation - Kik, Charles; van Valen, Richard; Mokhles, Mostafa M.; Bekkers, Jos A.; Bogers, Ad J. J. C. (The Thoracic and Cardiovascular Surgeon, 2017)
Minimally invasive video-assisted epicardial beating heart ablation for lone atrial fibrillation claims to be safe and effective. We, however, report on three patients with an atrioesophageal fistula after this procedure. The exact pathogenesis of this complication is unknown. All patients presented around 6 weeks after surgery with either fever or neurological deficits. Diagnosis can be made by computed tomography scan. We advocate an aggressive surgical approach with closure of the atrial defect on cardiopulmonary bypass and closure and reinforcement of the esophagus with an intercostal muscle flap in a single-stage surgery. Some caution as to the low-risk character of this procedure seems to be realistic.
Keywords: thoracoscopic ablation; atrioesophageal fistula; complication